The magnitude of second-trimester induced abortion and associated factors in Ethiopia: a systematic review and meta-analysis - Maru Mekie; Setegn Muche Fenta; Wassie Yazie Ferede; Enyew Dagnew Yehuala; Eyaya Habtie Dagnaw; Alemu Degu Ayele; Temesgen Dessie Mengistu; Belaynew Alemye Mengistie; Selamawit Girma Tadesse; Dagne Addisu (Frontiers in Global Women's Health, 2025)
BackgroundEven though Ethiopia has a non-restrictive abortion law, abortion complications are one of the top five maternal morbidity and mortality causes in the country. Most women visit health facilities for pregnancy termination at second-trimester which leads to higher abortion-related complications than first-trimester abortion. There is no national evidence regarding the level of second-trimester-induced abortion in Ethiopia. This study aimed to determine the magnitude of second-trimester induced abortion and its determinant factors.MethodsOnline searches using different online bases such as PubMed, HINARI, SCOPUS, Google Scholar, and University digital libraries were conducted to identify candidate studies to be included in this systematic review and meta-analysis. The Newcastle-Ottawa Quality Assessment Scale (NOS) was used to assess the quality of studies to be included in this review. Data extraction and analysis were performed using Microsoft Excel and Stata 17 software respectively. The heterogeneity of studies was assessed using Cochran (Q test) and I2 test statistics. We assessed publication bias using a funnel plot and Egger's regression asymmetry test.ResultsEight studies with a total study population of 3,659 were included in this review. The pooled prevalence of second-trimester induced abortion was 25.96% (95%, CI 14.42%, 37.49%) in Ethiopia. The finding of this systematic review indicated that being single [(OR = 5.20, 95%, CI 3.04, 8.90), I2 = 0.00%, p = 0.69], delay in the diagnosis of pregnancy [(OR = 3.01, 95%, CI 1.23, 7.38), I2 = 80.74%, p = 0.01], no formal/low education level [(OR = 3.54, 95%. CI 1.84, 6.78), I2 = 69.71, 57.15%, p = 0.04], and being rural resident [(OR = 2.16, 95%, CI 1.61, 2.92), I2 = 0.00%, p = 0.53] were factors significantly associated with second trimester induced abortion in Ethiopia.ConclusionThe prevalence of second-trimester abortion was found to be high in Ethiopia. Being single, delay in the diagnosis of pregnancy, having no formal/low education level, and being rural residents were factors significantly associated with second-trimester induced abortion in Ethiopia. Enhancing the sexual and reproductive health literacy of reproductive-age women as well as access to safe abortion services are relevant measures to be taken to reduce late visits to health institutions for abortion services.